Determining available potassium in soil by laser-induced breakdown spectroscopy combined with cation exchange membrane adsorption. Issue 11 (25th September 2020) - Fu, Xinglan; Zhao, Chunjiang; Ma, Shixiang; Tian, Hongwu; Dong, Daming; Li, GuangLin
Abstract : Potassium in soil is an essential nutrient for plants. Abstract : Potassium in soil is an essential nutrient for plants. However, the total potassium content of soil cannot be used to assess soil fertility and plant nutrition because not all of the potassium is available to plants. It is therefore necessary to determine the available potassium content of soil. Traditional methods for determining available potassium in soil are not suitable for rapid on-site use because they require complex sample treatments and numerous extractants, are time consuming, and use complex instruments. Laser-induced breakdown spectroscopy is fast, simple, and flexible. However, traditional laser-induced breakdown spectroscopy cannot distinguish between different forms of potassium in soil so cannot be used to determine available potassium. Here, we describe a new method involving laser-induced breakdown spectroscopy with cation exchange membrane adsorption for rapidly and accurately determining available potassium in soil. A good correlation was found between spectral intensity and the available potassium concentration. The coefficient of determination for the calibration curve was 0.99, the limit of detection was 2.2 mg kg −1, and the limit of quantitation was 7.3 mg kg −1 . Real soil samples were analyzed, and the average relative error between the predicted and reference concentrations was 2.58%. The extraction time was only 10 min. The method does not require chemical extractants like traditional methods for determining available potassium and is markedly faster and less complex than traditional methods. This is the first rapid laser-induced breakdown spectroscopy method for determining available potassium in soil.